TMT‐labeled quantitative proteomic analysis to identify proteins associated with the stability of peanut milk. (26th May 2021) - Jia, Cong; Lu, Xin; Gao, Jinhong; Wang, Ruidan; Sun, Qiang; Huang, Jinian
Abstract: BACKGROUND: Peanut milk benefits human health mainly due to its high protein content and suitable amino acid composition. To reveal the molecular mechanism affecting the quality of peanut milk, tandem mass tag (TMT)‐labeled proteomic analysis was applied to identify the proteome variation between two peanut cultivars that produced peanut milk with the best and worst stability. RESULTS: A total of 478 differentially abundant proteins (fold change >1.2 or <0.83, P  < 0.05) were identified. Most of these proteins were located in the cytoplasm and chloroplasts. Correlation analysis showed that RNA recognition motif (RRM) domain‐containing protein (17.1 kDa) had a negative relationship with the sedimentation rate of peanut milk and that 22.0 kDa class IV heat shock protein was negatively correlated with the creaming index ( P  < 0.05). Bioinformatic analysis showed that the molecular function of RRM domain‐containing protein (17.1 kDa) was associated with RNA binding and nucleotide binding, and 22.0 kDa class IV heat shock protein was involved in the pathway of protein processing in the endoplasmic reticulum. CONCLUSION: Overall, the differentially abundant proteins in the biological metabolic pathway might offer some potential markers to guide future peanut breeding, especially for the production of peanut milk. © 2021 Society of Chemical Industry.